Application of the Inquiry Method to Improve Learning Achievement in Digestive System Material - Mahnep Mahnep; José Antonio Arrueta; Monchai Tiantong; Seyed Masoud Hosseini; Nurul Azizah; Masooma Al Mutawah; Jutaro Sakamoto; Ensaf Nasser Al Mulhim (Tinta Emas Publisher, 2025)
The application of conventional methods such as lectures without using teaching aids can have a negative effect on students such as low student learning achievement. In the pre-cycle action, the average value of student learning achievement only reached 46.6%. Only 17 students out of 36 were declared to have achieved learning completeness. The application of the inquiry method can be a solution for teachers to improve student learning achievement. The purpose of this learning improvement is to improve the learning achievement of Class XI Matematika dan Ilmu Alam (MIA) 1 students of Sekolah Menengah Atas Negeri (SMAN) 9 Mataram. The subjects of this study were 21 students of Class XI MIA 1 SMAN 9 Mataram. Learning improvement actions were carried out in 3 cycles. The expected benefits of this study are: For teachers, it is expected to broaden their horizons and improve teacher professionalism, for students of course to improve their learning achievement, and for institutions or schools it is expected to be useful as an innovation in teaching and learning. The application of the inquiry method in learning shows that student learning achievement has increased significantly. In Cycle 1, the average value reached 56.6%, increasing to 63.6% in Cycle 2 and increasing again to 75.42% in Cycle 3. The results obtained from this learning improvement action are that inquiry learning can improve the learning achievement of Class XI MIA 1 SMAN 9 Mataram students in biology subjects in the 2023/2024 academic year.